Estimating Land Value Change Post Land Consolidation of Gadingsari Village, Bantul Regency, Special Region of Yogyakarta, Indonesia - Agatha - Astrisele; Purnama Budi Santosa (Jurnal Geospasial Indonesia, 2019)
Land is a resource with limited availability, but has an ever-increasing demand. Land Consolidation is a realignment activity which can be an alternative in planning a regional development. Land Consolidation in Gadingsari Village is a Bantul Regency government program implemented in 2017 located in Nanggulan, Patihan and Wonoroto Villages involving 200 land parcels , with 172 participants for land consolidation and 111,467 m2 of land. Land Consolidation produces land that has good accessibility and regularity of land parcels so it may triggers an increase in land value. An increase in land value can be estimated by modeling the land value before and after land consolidation. One method that is often used in the modeling of land values is the multiple variable linear regression method. The method used in this study involves the price of land as the dependent variable and the independent variable, namely: (1) Road Class; (2) Distance of land parcels to the Economic Center; (3) Distance of land parcels to the Village Government; (4) Distance between land parcels to the tourist site; (5) Distance of land parcels to Health Facilities; (6) Area; (7) Distance of parcels to Main roads; (8) Distance between land parcels of land to the beach; and (9) Land Use. The model formed is then used to calculate the estimated value of land prices before and after the implementation of land consolidation. The estimated value of land produced by the land value model prior to land consolidation ranges from Rp. 11,000 to Rp. 370,000. While the estimated land value for the land value model after land consolidation ranges from Rp. 21,000 to Rp. 605,000.